New challenges in psycholinguistics: Interactivity and alignment in interpersonal communication - Karpiński, Maciej (Lingua Posnaniensis, 2014)
In the present text, some recent changes in the perspective taken by psycholinguists in the study of language and communication are discussed. T heir interests seem to gradually shift from the study of language processing as an isolated and independent phenomenon towards inclusion of more interactional factors being indispensable components of interpersonal communication and involved in the process of communicative alignment. Alignment is here understood as a complex phenomenon that goes beyond increasing similarity of mental representations and related communicative behaviour. It simultaneously occurs on many levels and in various modalities, including those traditionally excluded from language study. A s a consequence, it implies not only more flexibility in the study of interpersonal communication but it also means a shift in the psycholinguistic methodology and probably also in the widely accepted picture of language and its limits.